Numerical simulation and analysis of the stress-strain state of the «lumbar spine – sacrum – pelvis» kinematic chain in unilateral blocking of the sacroiliac joint - Staude, Volodymyr; Kondratyev, Andrey; Karpinsky, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article deals with results of a numerical simulation and a mathematical analysis, using the finite element method, of the stress-strain state in the “lumbar spine – sacroiliac joint – pelvis” system with different variants of inclination of the sacrum and lumbar lordosis in conditions of unilateral blocking of the sacrum. Peculiarities of the maximum and minimum stress in the area of the sacroiliac joint in case of a unilateral blocking and different variants of inclination of the sacrum and lumbar lordosis are shown.